G1957C variation in Core Promoter and Precore/Core regions of Hepatitis B virus isolated from men who have sex with men (MSM) in Surakarta, Central Java, Indonesia - AFIONO AGUNG PRASETYO; RATNA SARIYATUN; ANGGA DWI PRASETYO; IBNU YUDISTIRO; RADEN ARTHESWARA SIDHAJATI (Smujo International, 2014)
Abstract. Prasetyo AA, Sariyatun R, Prasetyo AD, Yudistiro I, Sidhajati RA. 2014. G1957C variation in Core Promoter and Precore/Core regions of Hepatitis B virus isolated from men who have sex with men (MSM) in Surakarta, Central Java, Indonesia. Nusantara Bioscience 6: 107-110. Little is known about HBV isolates in Indonesian men who have sex with men (MSM) community. Thus, this study was aimed to analyze the genetic profile of HBV isolated from MSM in Indonesia, particularly in Surakarta, Central Java. A total of 205 blood samples were examined by polymerase chain reaction (PCR) targeting the partial Core Promoter (CP) and Precore/Core (preC/C) regions. Three samples were found positive by PCR. The amplicons were sequenced and subjected to molecular analysis. The genetic profile of all HBV isolated in Indonesia (n= 122) was also included for molecular analysis. All HBV isolated from the MSM were genotype B3. G1957C (C195S) was found in all HBV isolated from the MSM community and subject with sex with man history. Several disease-related mutations were observed among HBV sequences from Indonesia, including T1753C, A1762T, G1764A, A1846T, and G1896A which existed in 7.2% (9/125), 17.6% (22/125), 19.2% (24/125), 16.8% (21/125), and 24.8% (31/125) sequences, respectively; however, none were present in HBV isolated from the MSM. In conclusion, various mutations, including those related to disease, were found in Indonesian HBV isolates. G1957C variation was unique in the HBV isolated from the MSM.